Investigating the Discriminant Utility of Task-Based and Self-Based Goals in 3 × 2 Achievement Goal Model for Kindergarteners - Chung-Chin Wu (MDPI AG, 2022)
A decade ago, achievement goal theorists argued that mastery-based goals in the traditional theoretical framework can be theoretically differentiated into task-based goals and self-based goals; and they proposed the 3 × 2 achievement goal model to understand students' achievement motivation. This new theoretical model has received increasing attention, and it has been demonstrated by several empirical studies on school-aged student samples through analyzing concurrently derived data. Recently, researcher has preliminary demonstrated the new theoretical model on kindergarten sample. It is unclear whether there was a discriminant utility of these goals for kindergartener sample through analyzing their concurrent and predictive effects on learning outcomes. The main purposes of this study were to investigate discriminant utility of task-based goals and self-based goals through examining their concurrent and predictive effects on mathematics performances. A total of 59 kindergarteners aged 5 years consented to participating in this study. Results showed: (1) The discriminant utility of task-approach goal and self-approach goal was only demonstrated on predictive arithmetic performance. (2) The discriminant utility of task-avoidance goal and self-avoidance goal was demonstrated on both concurrent and predictive counting performances. Implications for advancing achievement goal theory, future research, and practice are discussed at the end of the article.